Disparities in Mental Health Referral and Diagnosis in the New York City Jail Mental Health Service - Kaba, Fatos (Am J Public Health, 2015)
Objectives. To better understand jail mental health services entry, we analyzed diagnosis timing relative to solitary confinement, nature of diagnosis, age, and race/ethnicity. Methods. We analyzed 2011 to 2013 medical records on 45 189 New York City jail first-time admissions. Results. Of this cohort, 21.2% were aged 21 years or younger, 46.0% were Hispanic, 40.6% were non-Hispanic Black, 8.8% were non-Hispanic White, and 3.9% experienced solitary confinement. Overall, 14.8% received a mental health diagnosis, which was associated with longer average jail stays (120 vs 48 days), higher rates of solitary confinement (13.1% vs 3.9%), and injury (25.4% vs 7.1%). Individuals aged 21 years or younger were less likely than older individuals to receive a mental health diagnosis (odds ratio [OR] = 0.86; 95% confidence interval [CI] = 0.80, 0.93; P < .05) and more likely to experience solitary confinement (OR = 4.99; 95% CI = 4.43, 5.61; P < .05). Blacks and Hispanics were less likely than Whites to enter the mental health service (OR = 0.57; 95% CI = 0.52, 0.63; and OR = 0.49; 95% CI = 0.44, 0.53; respectively; P < .05), but more likely to experience solitary confinement (OR = 2.52; 95% CI = 1.88, 3.83; and OR = 1.65; 95% CI = 1.23, 2.22; respectively; P < .05). Conclusions. More consideration is needed of race/ethnicity and age in understanding and addressing the punishment and treatment balance in jails.